The implications of husband's education on expectant's delivery planning in Salatiga - Sri Drisna Dewi; Citra Indriani; Shinta Prawita Sari (Berita Kedokteran Masyarakat (BKM), 2016)
Purpose: The purpose of this paper is to determine the implications of husband’s education on expectant’s delivery planning.Method: A cross-sectional study was conducted involving 267 expectant on the third trisemester in Salatiga.Findings: The study found that 85.4% of respondents planned to deliver well. The results of the analysis indicated that there was a significant relationship between husband's education variable OR = 2.62 (95% CI: 1,20-5,58 p = 0,0061). The result of potential confounder test shows that husband knowledge has OR crude = 2,62 and OR M-H = 2,32 with change value of 12.21%. it is clear that husband's knowledge has an influence on the relationship of husband's education with maternity delivery planning.Conclusion: The higher husband’s education level, the better the maternity planning of pregnant women, the multiparous parity had a better maternity planning then primiparous parity and a high-risk factor status of pregnant women will plan better maternity than low-risk status. It is expected for pregnant women and her husband to be more active in seeking information about P4K.